Urban and rural residence: their influence on food group consumption in Iran - Susan Darroudi; Sara Saffar Soflaei; Farzam Kamrani; Zahra Khorasanchi; Zahra Abdollahi; Nasrin Talkhi; Maryam Allahyari; Seyyed Reza Sobhani; Maryam Mohammadi-Bajgiran; Amirmohammad Naderkhmseh; Maliheh Aghasizadeh; Habibollah Esmaily; et al. (BMC Public Health)
Abstract Background Urbanization is expanding in Iran, leading to the emergence of three distinct socio-geographical areas: urban, rural, and suburban areas. These different areas may exhibit significant variations in dietary patterns. This study investigates the association between people’s place of residence and their consumption of different food groups. Methods This study utilized data from Iran’s Food and Nutrition Surveillance System (FNS). A total of 1697 participants were randomly recruited from different rural (N = 568), urban (N = 568), and suburban (N = 561) regions across Iran. Their food intake was assessed using a validated dish-based semi-quantitative food frequency questionnaire (DB-FFQ). Results Rural males consumed significantly more grains (35.51 g/day, p = 0.03) than urban males, while rural females consumed significantly less dairy (-30.07 g/day, p = 0.03) than urban females. Additionally, rural males and females consumed significantly more fats and oils (3.72 g/day, p = 0.01 for males and 5.2 g/day, p < 0.001 for females) than their urban counterparts. Moreover, both suburban females and males were found to consume significantly less fruit compared to urban individuals, with suburban females consuming − 47.41 g/day (p < 0.001) less fruit and suburban males consuming − 60.42 g/day (p = 0.001) less fruit. Conclusion Findings showed that rural men’s diets are characterized by higher consumption of grains and fats, while urbanization is linked to increased dairy consumption in women. Additionally, the study highlights a worrying lack of fruit consumption in suburban areas. These findings underscore the necessity of implementing specific nutritional policies to promote dietary diversity in various residential areas. Graphical Abstract